2022
DOI: 10.12688/gatesopenres.13347.2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influence the local establishment of Wolbachia in Aedes aegypti mosquitoes in two small communities in central Vietnam

Abstract: Background: The wMel strain of Wolbachia has been successfully introduced into Aedes aegypti mosquitoes and subsequently shown to reduce transmission of dengue and other pathogens, under both laboratory and field conditions. Here we describe the entomological outcomes of wMel Wolbachia mosquito releases in two small communities in Nha Trang City in central Vietnam. Methods: The wMel strain of Wolbachia was backcrossed into local Aedes aegypti genotype and mosquito releases were undertaken by community members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…aegypti into two small communities in Nha Trang City in central Vietnam resulted in a seasonal heterogeneity of w Mel invasion and spread into the local Ae . aegypti populations with a reduced prevalence of Wolbachia infection in mosquitoes during the hot dry season, followed by an increased prevalence during the cooler season, and such seasonal variation in Wolbachia infection prevalence in mosquitoes was associated with elevated temperature and was possibly due to imperfect maternal transmission of Wolbachia [ 36 ]. These studies suggested that the maternal transmission of the two Wolbachia strains can become unstable in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti into two small communities in Nha Trang City in central Vietnam resulted in a seasonal heterogeneity of w Mel invasion and spread into the local Ae . aegypti populations with a reduced prevalence of Wolbachia infection in mosquitoes during the hot dry season, followed by an increased prevalence during the cooler season, and such seasonal variation in Wolbachia infection prevalence in mosquitoes was associated with elevated temperature and was possibly due to imperfect maternal transmission of Wolbachia [ 36 ]. These studies suggested that the maternal transmission of the two Wolbachia strains can become unstable in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti for population replacement is now underway in 11 countries to evaluate its effectiveness in controlling dengue (World Mosquito Program [WMP], 2022). This strain has successfully been established in Australia (O'Neill et al, 2018;Ryan et al, 2020), Brazil (Pinto et al, 2021), Indonesia (Utarini et al, 2021), and Vietnam (Hien et al, 2022), while wAlbB was successfully established among wild mosquito population in Malaysia for population replacement (Nazni et al, 2019). In a recent randomized control trial in Yogyakarta city, Indonesia, field releases of wMel-infected Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that w AlbB is more stable at high temperature than w Mel in Ae. aegypti , leading to the proposed release of w AlbB in areas where it is challenging for w Mel to establish infection because of its high susceptibility to extreme summer temperatures and wide yearly temperature ranges ( 41–43 ). Based on analysis of the w AlbB whole-genome sequence, only four single nucleotide variants have occurred over 15 years of transinfection ( 43 ).…”
Section: Introductionmentioning
confidence: 99%